Genetic engineering of pigs for xenotransplantation to overcome immune rejection and physiological incompatibilities: The first clinical steps - Lei, Tiantian; Chen, Lin; Wang, Kejing; Du, Suya; Gonelle-Gispert, Carmen; Wang, Yi; Buhler, Leo H. (Frontiers in Immunology, 2022)
Xenotransplantation has the potential to solve the shortfall of human organ donors. Genetically modified pigs have been considered as potential animal donors for human xenotransplantation and have been widely used in preclinical research. The genetic modifications aim to prevent the major species-specific barriers, which include humoral and cellular immune responses, and physiological incompatibilities such as complement and coagulation dysfunctions. Genetically modified pigs can be created by deleting several pig genes related to the synthesis of various pig specific antigens or by inserting human complement‐ and coagulation‐regulatory transgenes. Finally, in order to reduce the risk of infection, genes related to porcine endogenous retroviruses can be knocked down. In this review, we focus on genetically modified pigs and comprehensively summarize the immunological mechanism of xenograft rejection. We also describe recent progress in preclinical pig-to-nonhuman primate studies and in clinical studies, especially in recent cases of porcine organs transplanted to human patients. Overall, both genetically engineered pig-based xenografts and technological breakthroughs in the biomedical field provide a promising foundation for pig-to-human xenotransplantation in the future.